Educational Crisis and Reform : Perspectives from South Asia - Edited by Rashid, Abbas & Muzaffar, Irfan (Karachi Oxford University Press, 2015)
Comprising of contributions from India, Pakistan, Bangladesh, Sri Lanka, and Nepal, this book examines the attempts to reform specific aspects of the education sector of the above-mentioned countries of South Asia.
Include Index